Perancangan Aplikasi Pengolahan Data Logistik pada Kantor Cabang Bri Solok - Cendra Wadisman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
With the development of information technology companies are required to improve the efficiency and quality of service. The logistics department not only serves to support the office operations but one of the functions that will improve the effectiveness and efficiency of the company. This research was conducted to assist the logistics department in making efficient use of time, energy and cost in making logistic report at Bank Rakyat Indonesia branch of Solok. In this research will be made data processing logistics system using Java programming language and MySQL database. Based on data obtained by way of observation and interview further data analyzed to make system design as needed. Keywords : Data Processing Logistics, JAVA, MYSQL